A systematic literature review on the benefit-drivers of RFID implementation in supply chains and its impact on organizational competitive advantage - Janya Chanchaichujit; Sreejith Balasubramanian; Ng Si Min Charmaine (Cogent Business & Management, 2020)
Application of Radio Frequency Identification (RFID) in managing supply chains has witnessed significant interest in recent years. However, the current understanding of the potential benefits that act as the motivating factors/drivers in implementing RFID technology (benefit-drivers), its link to competitive advantage, is fragmented and scattered across the literature. This formed the motivation of this study which seeks to address this gap in the literature through a systematic literature review. Based on a rigorous screening of the literature (2006-2018), the study develops a comprehensive understanding of the various 1) corporate-driven and 2) customer-driven benefit-drivers from RFID implementation. The "2 C" categorization of benefit-drivers is novel and should provide more impetus for practitioners to leverage from RFID implementation. Further, the link between the benefit-drivers and competitive advantage is understood and proposed in the form of a conceptual framework. Finally, avenues for future research are highlighted. The study findings and the framework provide a good starting point for academics and practitioners to further explore the opportunities in supply chain afforded by RFID implementation. A comprehensive review of this kind has not been previously undertaken and constitutes the novelty of this work.
Keywords: 650; Radio Frequency Identification (RFID); supply chain management; conceptual framework drivers; benefits; tracking; visibility; competitive advantage